Strawberry (Fragaria ananassa) seedlings formation under different intensities of violet, blue and red LED light - Ruiz Nieto, Jorge Eric (2024)
Introduction. Seedlings formation under controlled conditions is crucial for cultivating species like strawberry. With LED artificial lighting technology allowing greater control over light, variations in components such as wavelength and intensity can be manipulated to generate seedlings with different characteristics. However, there is a need to generate information for the development of precise and efficient light control practices. Objective. The evaluate strawberry seedling formation under different intensities of violet, blue, and red LED light. Material and methods. The study was conducted in 2020 at the Plant Genetics Laboratory of the Department of Agronomy at the Universidad de Guanajuato, Guanajuato, Mexico. Seeds from San Andreas variety fruits were collected, and seedlings were grown under violet, blue, and red LED light at high, medium, and low intensities. Color determinations of cotyledon area, Chroma saturation index, and Hue angle were performed. Additionally, physio-technical, chemical, and antioxidant activity variables were measured. Results. The most suitable treatments were high and medium intensity violet light, as well as high intensity blue light, with germination range exceeding 60 %. Seedlings did not elongate or thin out and exhibited the largest cotyledons areas and chlorophyll concentrations. Furthermore, these light treatments consumed, on average, 31.2 % less electrical energy. Conclusions. In addition to white light, the most suitable treatments for strawberry seedlings formation were high and medium intensity violet light, as well as high intensity blue light. It is suggested to evaluate violet and blue light treatments in other cultivars to confirm their positive effect on strawberry seedlings. Red light limited germination and showing higher antioxidant activity.